Pain relief outcomes using an SCS device capable of delivering combination therapy with advanced waveforms and field shapes. (1st September 2020) - Metzger, Clark S.; Hammond, M. Blake; Pyles, Stephen T.; Washabaugh, Edward P.; Waghmarae, Romanth; Berg, Anthony P.; North, James M.; Pei, Yu; Jain, Roshini
ABSTRACT: Background: Given the range of subjective experiences reported by patients with chronic pain, Spinal Cord Stimulation (SCS) systems designed for tailored delivery of analgesic therapy may help improve treatment effectiveness and satisfaction. Research design and methods: This case-series evaluated 420 patients with chronic back and/or leg pain implanted with an SCS device capable of sequential or simultaneous delivery of neurostimulation (i.e. combination therapy) as well as multiple waveforms and/or field shapes. Following implantation, an array of standard programs (e.g. paresthesia-based SCS), and a custom set of sub-perception programs were provided per patient feedback. Pain scores (Numeric Rating Scale, NRS) were collected at baseline and during follow-up. Results: In this multicenter, observational series (n = 420, 53.1% female; Age: 64.2 ± 13.4 years), a mean overall pain score of 7.2 ± 1.8 (SD) was reported pre-trial (Baseline). At a mean follow-up duration of 208 ± 200 (SD) days, the mean overall pain score reduced to 2.4 (p < 0.0001). Overall pain was reduced by 5.1 ± 2.4 and 4.5 ± 2.4 points (NRS) at 3-months (N = 256) and at 12-months post-implant (N = 122) respectively (p < 0.0001). Conclusions: These results suggest that highly 'customizable' SCS approaches may allow for highly effective pain relief within the real-world clinical setting.